Formation of climate coalitions and preferential free trade - The case for participation linkage - Thomas Kuhn; Radomir Pestow; Anja Zenker (Chemnitz University of Technology, Faculty of Economics and Business Administration, 2022)
We study the endogenous formation of climate coalitions linked to a preferential free trade arrangement. In a multi-stage strategic trade and participation game, coalition and fringe countries dispose of a discriminatory tariff on dirty imports as well as emission permits imposed on domestic producers and traded on a common permit market inside the coalition, or respectively local markets outside. The participation game is solved by Monte-Carlo simulation, while the general equilibrium and the policy game are solved analytically. We find that preferential free trade can create effective climate coalitions in terms of depth and breadth.
Keywords: Q54; Q56; F18; F15; Q58; 330; Climate Change; International Environmental Agreements; Preferential Free Trade; Issue Linkage; Emission Permits